Phenotypic Variation of Cell Wall Composition and Stem Morphology in Hemp (Cannabis sativa L.): Optimization of Methods - Petit, Jordi; Gulisano, Agata; Dechesne, Annemarie; Trindade, Luisa M. (Frontiers in Plant Science, 2019)
The growing demands for sustainable fibres have stimulated the study of genetic diversity in the quality of hemp fibre (Cannabis sativa L.). Nevertheless, the lack of high-throughput phenotyping methods that are suited for the analysis of hemp fibre, hampers the analysis of many accessions, and consequently the breeding for this complex trait. In the present report, we developed and optimized the throughput of five methods to study the diversity in hemp fibre quality including cell wall extraction, biochemical composition of cell wall polysaccharides, quantification of lignin, quantification of crystalline polysaccharides and morphology of the stems. Six hemp accessions contrasting for cell wall properties were used to assess the throughput and suitability of these methods for genetic studies. The methods presented revealed to be highly repeatable, with low coefficients of variation between technical replicates. With these methods we were able to detect significant phenotypic variation in cell wall composition and stem morphology between the six accessions. In addition, the throughput of the methods has been upgraded to a level that enables their use for phenotyping cell wall traits in breeding programs. The cell wall extraction was optimized to extract enough material for the complete characterization of the cell wall of hemp while reducing the time for the entire analysis. The throughput of the stem morphological analysis was improved by decreasing the timing of fixation, infiltration and embedding of mature and dry hemp stems. Notwithstanding, our methods already have the potential to phenotype large number of accessions in a relatively short period of time. Our methods will enable exploration of genetic diversity of fibre quality and will contribute to the development of new hemp varieties with advanced quality of fibres.